Influence of Prosthetic Crowns on Gingival Fluid - Robo Ilma; Qafmolla Ruzhdie (Balkan Stomatological Society, 2015)
Purpose: Evaluation of the impact that a foreign body has in the gingival sulcus, expressed in scale to cause significant gingival infection.